Effects of structured exercise among overweight and obese female Malay participants on health related fitness - Yen, Wong Foo (Pusat Pengajian Sains Kesihatan, 2014)
Regular participation in physical activity can improve physical fitness such as health-related fitness and skill-related fitness. A lot of studies were conducted with various mode of exercise including dumbbell exercise, resistance training, circuit training, aerobic exercise and so on but study into structured exercise especially on overweight and obese population is scarce. The purpose of this study is to investigate the effects of structured exercise among overweight and obese female Malay participants on health related fitness. Thirteen (n=13) female Malay-ethnic participants with age above 21 years old were recruited in this study. Participants were required to undergo a preintervention (PR) health-related fitness testing which included muscular strength, muscular endurance, cardiovascular fitness, flexibility, body composition with additional of resting heart rate, systolic and diastolic blood pressure. All participants followed a prescribed and supervised exercise starting from the day after the PR health-related fitness testing of three sessions of dumbbell exercise (45 minutes / session), and one sessions of aerobic exercise (1 hour / session) on alternate day each week for the duration of three months and dietary, health and lifestyle educational counseling (15 minutes / session) after each session of dumbbell exercises. In addition, all participants were required to record their daily dietary intake and physical activity other than the prescribed exercises. After three months of intervention with structured exercise, all participants were required to undergo a post health-related fitness testing, which is identical to the PR health-related fitness testing. The post-intervention (PO) health-related fitness testing results is then compared with PR health-related fitness testing results to see whether there is any improvement in any measures. The results of this study indicated that cardiovascular fitness (PR: 36.26 ± 8.87; PO: 39.21 ± 6.64 mL 02 kg'1 min'1), waist circumference (81.50 ± 13.1; 80.00 ± 11.0 cm), estimation of body fat percentage (36.65 ± 3.9; 35.30 ± 3.8 %), systolic and diastolic blood pressure (120 ± 17 / 80 ± 14; 117 ± 22 / 73.5 ± 13 mm Hg) were found to be statistically significant in difference (p<0.05) between the post-intervention and pre-intervention of health-related fitness testing. On the other hand, there was no significant difference (p>0.05) statistically in muscular strength (back and leg strength [45.00 ± 45; 60.00 ± 60 kg]; handgrip strength: left [26.00 ± 14; 28.00 ± 13 kg]; right [28.00 ± 10; 28.00 ± 14 kg]), muscular endurance (sit-up per minute [17.00 ±11; 16.00 ± 10 times per minute]; push-up per minute [16.00 ± 8; 17.00 ± 6 times per minute]), flexibility (7.50 ± 8.3; 8.50 ± 6.6 cm), resting heart rate (81.00 ± 15; 79.50 ± 15 beats per minute), hip circumference (100.00 ± 12.8; 102.50 ± 10.8 cm), waist-hip ratio (0.78 ± 0.07; 0.77 ± 0.08), weight (65.80 ± 19.3; 65.45 ± 16.2 kg), height (1.55 ± 0.09; 1.55 ± 0.09 m) and body mass index (27.70 ± 5.5; 28.00 ± 5.5) between the post-intervention and pre-intervention of health-related fitness testing. The results revealed that intervention of short term (3 months) structured exercise helps in improving cardiovascular fitness, decreasing waist circumference, estimation of body fat percentage, systolic and diastolic blood pressure while it might be less effective in improving muscular strength, muscular endurance, flexibility, resting heart rate, hip circumference, waist-hip ratio, weight, height and body mass index. Further study should be done to confirm the results and to gain a more insightful into mechanism of how structured exercise and surrounding factors interacts.